Frequencies and predominant periods of earthquakes registered in the city of Tacna, by means of analysis and Fourier spectrum - Mendoza Ramirez, Wilber (2020)
The city of Tacna is in seismic silence, waiting for a large earthquake and the environmental effects that this causes. The objective of the investigation was to determine the prevailing frequencies and periods of some earthquakes registered in the city of Tacna, using the Fourier analysis and spectrum. Earthquakes of the present century, of a magnitude greater than 5.0 Mw and from different near, intermediate and distant seismogenic sources were selected. The research used the Fourier mathematical model to process seismic signals, from the time domain to the frequency domain, then, the prevailing frequencies and periods of the different signals were analyzed and learned. For better signal processing, a code was created in Matlab to perform the calculations, which were then verified using the Seismosignal software. The predominant frequencies of earthquakes from close sources vary from 2.12 to 11.43 Hz (predominant periods from 0.09 to 0.47 s); earthquakes of intermediate source, vary from 5.15 to 11.29 Hz (predominant periods from 0.09 to 0.19 s); and earthquakes from distant sources, vary from 0.43 to 6.06 Hz (predominant periods from 0.17 to 2.34 s). As most of the earthquakes had predominantly short periods, these could generate resonance phenomena to structures with periods of vibration less than 0.5 s.